Territorial governance. Dialogue with agricultural producers in northwestern Mexico (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2024)
The structure of the Mexican countryside was substantially modified with the reforms to Article 27 of the Mexican Constitution in the 1990s, intensifying the challenge of rural governance. This article analyzes the governance actions carried out by actors in the Yaqui Valley, which promote forms of organization based on five dimensions: 1) coordination 2) horizontality 3) bonds of trust 4) conflict and 5) environment. For data collection, seven producer organizations were interviewed on farmlands and complemented with field notes and observation. The analysis of the results shows two governance models: the first is characterized by association, working together or in partnership, while the second stands out for the independence of the producer and maintains little association. Both models present advantages and disadvantages; however, the collective form of organization, as opposed to the individual one, shows a better performance. It is concluded that territorial governance could be considered an alternative in the design of public policies that promote economic and social development, based on the recognition of actors, the particularities of the territory and the institutional environment.
Keywords: Forms of organization; governance; territory; institution; Yaqui Valley